Sound-changes and loanwords in Sungai Penuh Kerinci - Steinhauer, Hein (UI Scholars Hub, 2018)
In this paper I shall (re)analyse the historical development of the Sungai Penuh variety of Kerinci in terms of sound-changes, with special attention to forms which deviate from the more common patterns. Data for this study have been taken from the stencilled version of Amir Hakim Usman’s Kerinci-Indonesian dictionary (1976) with handwritten annotations by the author, the late David John Prentice, and myself, the result of elicitation sessions with the author in 1977 in Leiden. Some additional data derived from Usman 1988 and from an interview with the author in 1999.